-2(t-5)+6t=8t-8

Simple and best practice solution for -2(t-5)+6t=8t-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(t-5)+6t=8t-8 equation:


Simplifying
-2(t + -5) + 6t = 8t + -8

Reorder the terms:
-2(-5 + t) + 6t = 8t + -8
(-5 * -2 + t * -2) + 6t = 8t + -8
(10 + -2t) + 6t = 8t + -8

Combine like terms: -2t + 6t = 4t
10 + 4t = 8t + -8

Reorder the terms:
10 + 4t = -8 + 8t

Solving
10 + 4t = -8 + 8t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-8t' to each side of the equation.
10 + 4t + -8t = -8 + 8t + -8t

Combine like terms: 4t + -8t = -4t
10 + -4t = -8 + 8t + -8t

Combine like terms: 8t + -8t = 0
10 + -4t = -8 + 0
10 + -4t = -8

Add '-10' to each side of the equation.
10 + -10 + -4t = -8 + -10

Combine like terms: 10 + -10 = 0
0 + -4t = -8 + -10
-4t = -8 + -10

Combine like terms: -8 + -10 = -18
-4t = -18

Divide each side by '-4'.
t = 4.5

Simplifying
t = 4.5

See similar equations:

| 2(3x-1)(x+5)= | | d--3=5 | | x=100y+-400 | | 5[3+2(4)]-45= | | 11(4x+12)= | | -32+16y=16 | | q-10=7 | | 11(6x+11)= | | x=1000+-100y | | 2x+40=8x+4 | | x=1000-100y | | 17+3=11g+39 | | 8(2m+4)+3(m-2)+16= | | 4x=6x-45 | | 50=2(w-5)+2w | | -4(3p+9)= | | 14x^2-42x= | | -14y=12x-28 | | 6(2x+5)+5(2x+7)= | | 19m+42= | | 100x-x=14 | | 7f+5=5f+17 | | 41x=14 | | I=(89)(.075)(.5) | | 4x-6x+2x-8x= | | 3x+(2x+10)=5 | | 18s=10 | | (8x+22)=(5x+15) | | 0.4*x=X-100 | | 18+6.50(x-3)= | | 725.4656=4*3.14*r^2 | | 4392.1064=4*3.14*r^2 |

Equations solver categories